Determinan Penggunaan Informasi Akuntansi Pendidikan Anak Usia Dini - Animah, Animah; Suryantara, Adhitya Bayu; Astuti, Widia (E-Jurnal Akuntansi, 2022)
This study aims to examine the determinants of the use of PAUD accounting information in the city of Mataram. This test was conducted on 124 PAUD respondents in the city of Mataram. The survey was conducted to determine the correlation between the research variables. Quantitative-based research with primary data sources and variant-based SEM (SEM PLS) methods with the Smart PLS 3.0 application software as a data processing technique. The results of the study show that accounting knowledge and experience with accounting information have an effect on the use of accounting information. On the other hand, company size, accounting education, and owned software and hardware do not affect the application of accounting information. Keywords: Firm Size; Accounting Training; Accounting Knowledge; Experience; Conditions that Fasilitated the Users.